A survey of e-learning security - Mandala, Satria (2013)
E-learning is one of the most powerful responses to the growing need for education. It could be as effective as conventional face to face classroom learning under certain situation. Some researchers have proved that e-learning has a positive impact not only for learners, but also for instructors and providers. In fact, e-learning reduces costs, time and improves the performance of learning. However, most of e-learning systems are vulnerable to many attacks. This paper surveys the current protections to address the vulnerabilities of the e-learning systems. It also provides a categorization to the e-learning protections based on source of vulnerabilities.